1986
DOI: 10.1002/jso.2930320412
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma complicating late chronic discoid lupus erythematosus

Abstract: Two cases of squamous cell carcinoma developing in lesions of chronic cutaneous discoid lupus erythematosus are presented. One of the patients was white and the other was black. The squamous cell carcinoma in the black patient proved to be rapidly metastatic and eventually fatal. The white patient developed seven squamous cell carcinomas over 8 years with no evidence of metastatic spread. The role of ultraviolet light in inducing skin cancer in these patients is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Dabski et al [9] and Martin and Rosen [10] reported that there was high metastatic potential in squamous cell carcinomas that arise in DLE. Most of the authors preferred excision as treatment if a squamous cell carcinoma complicated DLE [1].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Dabski et al [9] and Martin and Rosen [10] reported that there was high metastatic potential in squamous cell carcinomas that arise in DLE. Most of the authors preferred excision as treatment if a squamous cell carcinoma complicated DLE [1].…”
Section: Discussionmentioning
confidence: 97%
“…Exposure to actinic radiation [1], and carcinogenic agents such as cytotoxics or radiation [8] were the main causes in this case. Reports of squamous cell carcinoma on a DLE lesion are common [9]. In recent years, the reduction in the incidence of squamous cell carcinoma with DLE was explained by changes in the treatment of the DLE, with the omission of carcinogenic agents [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6][7] Confusion with squamous cell carcinoma may be especially troublesome, for the occurrence of indubitable squamous cell carcinoma arising in lesions of DLE is well described. [8][9][10][11][12][13][14][15][16][17] Nonhypertrophic and atrophic lesions of CLE can exhibit similar atypical changes and may also mimic squamous neoplasia. When keratinocytic atypia and dyskeratosis are present in such lesions, actinic keratosis, lichen planuselike keratosis, and squamous cell carcinoma must be included in the differential diagnosis.…”
mentioning
confidence: 99%